Post‐transplant maintenance therapy in patients with FLT3‐mutated acute myeloid leukemia: Real‐world treatment patterns and outcomes. (11th August 2021) - Griffin, James D.; Song, Yan; Yang, Hongbo; Freimark, Jonathan; Shah, Manasee V.
Abstract: Objectives: Maintenance therapy is one strategy to prolong survival in patients with acute myeloid leukemia (AML) following hematopoietic stem cell transplantation (HSCT). We evaluated real‐world treatment patterns and outcomes in patients with newly diagnosed FLT3 ‐mutated AML receiving HSCT after complete remission with first‐line chemotherapy. Methods: A global, retrospective chart review to evaluate maintenance therapy and outcomes in patients with FLT3 ‐mutated AML after HSCT. Results: Data from 1208 charts from eight countries showed that most patients (n = 765 [63.3%]) received no maintenance therapy after HSCT, 219 (18.1%) received FLT3 inhibitor maintenance therapy, and 224 (18.5%) received other types of maintenance therapy. No systematic differences were observed in healthcare resource utilization across the three groups. Clinical benefit was observed with FLT3 inhibitor maintenance over no maintenance therapy with relapse‐free survival (adjusted hazard ratio [HR] 0.57 [95% CI 0.34‐0.94], P < .05). FLT3 inhibitor and other maintenance also demonstrated overall survival benefit over no maintenance (adjusted HR 0.50 [95% CI 0.28‐0.89] and 0.46 [95% CI 0.23‐0.91], respectively; both P < .05). Conclusions: Real‐world maintenance therapies after HSCT in patients with FLT3 ‐mutated AML were heterogeneous. While overall use of healthcare resources was not significantly increased in patients receiving maintenance therapy versus those who did not, clinical outcomes were improved.